Persepsi mahasiswa PPKn terhadap fenomena flexing dan kesenjangan sosial di lingkungan kampus - Marnisa Hidayah; Maria Montessori; Hasrul Hasrul; Eni Kurniawati (Journal of Education, Cultural and Politics, 2026)
This study aims to analyze students’ perceptions of the flexing phenomenon and social inequality in the campus environment. The research was conducted among students of the Pancasila and Civic Education Study Program, Faculty of Social Sciences, Universitas Negeri Padang. This study employed a quantitative approach using a descriptive method. The population consisted of 333 students from the 2022, 2023, and 2024 cohorts, with a sample of 182 students selected using purposive sampling techniques. The research instrument was a questionnaire developed based on three indicators of perception: cognitive, affective, and conative aspects. Data were collected through questionnaires and analyzed using percentage analysis. The results showed that students’ perceptions in the cognitive aspect were in the good (78%) and very good (18%) categories, the affective aspect was in the good category (76%), and the conative aspect was in the very good (52%) and good (45%) categories. These findings indicate that students have a good understanding, positive attitudes, and appropriate behavioral tendencies in responding to the flexing phenomenon and social inequality. Therefore, it can be concluded that students are able to respond critically and wisely in accordance with social values in the campus life.